Analysis of Children’s Numeracy Skills in The Village Pagar Dewa Kaur with Math Approach Realistic - Jessica Adelia Saputri; Resti Komala Sari; Uwe Barroso; Eladdadi Mark (Yayasan Adra Karima Hubbi, 2023)
Background. The relevance of math materials to children's daily lives is an important factor in the success of this approach. Purpose. This study aims to analyze the counting ability of children in Pagar Dewa Village Kaur with Realistic Mathematics approach. Method. The research sample consisted of 30 children aged 6-8 years. Data was collected through counting ability test and observation. Results. he results showed that most of the children in Pagar Dewa Village Kaur had low counting skills. However, after learning with the Realistic Mathematics approach, there was a significant increase in children's understanding and application of mathematical concepts. Conclusion. This study provides recommendations for educators and curriculum developers to apply the Realistic Mathematics approach in children's mathematics learning in rural areas.